HUKUM ISLAM INKLUSIF DI MASA DEPAN: ANALISIS PEMIKIRAN ABDULLAH AHMED AN-NA’IM TENTANG DEKONSTRUKSI SYARIAH - Cynthia Nur Rasyid; Achmad Fageh (STIS MIFTAHUL ULUM LUMAJANG PRESS (STISMU PRESS), 2025)
The study of Islamic law has great significance to continue to be studied in depth because its discussion is always a topic of debate. In addition, Islamic law needs to develop along with the changing times. This article aims to understand three main aspects: first, an overview of an-Naim's thoughts regarding Islamic law (sharia); second, the methodological approach used to reformulate sharia; and third, the vision of inclusive Islamic law in the future, which is able to adapt to the social dynamics of society. This study uses a literature study method by analyzing texts from various books and articles. Data are analyzed through the stages of selection, classification, analysis, and verification. The results of the study show that: (1) According to an-Naim, sharia does not only focus on the texts of the Qur'an and Sunnah, but must be reinterpreted according to the context and reality of the present. (2) An-Naim uses the naskh-mansukh method, namely by postponing the application of verses that are considered less relevant without permanently deleting them. (3) An-Naim's idea of ​​inclusive Islamic law emphasizes the importance of equality for all human beings, including in religious, ethnic, and racial aspects, and involves reforms in criminal law, human rights, and international relations. In conclusion, Islamic law can be universally accepted as a model that reflects progress and harmony with human life, thus providing significant benefits, both in the Islamic world and globally. Keywords : Islamic Law, Inclusive, Abdullah Ahmed An-Na’im